2023
DOI: 10.1037/fam0001014
|View full text |Cite
|
Sign up to set email alerts
|

Linking early head start children’s social–emotional functioning with profiles of family functioning and stress.

Abstract: This study examined profiles of family functioning, stress, psychological well-being, and social support in families participating in early head start; family characteristics that relate to profile membership; and the relationship of profiles to child social–emotional functioning. Because families’ levels of functioning and well-being vary widely within low-income samples, we used a person-centered approach to understand how variations among families are linked with children’s social–emotional skills. Our late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…Structural barriers impact family involvement in programming, including a lack of flexibility in parents’ work schedules and difficulty arranging family involvement activities outside of program hours (Golas et al, 2006 ; Spoth & Redmond, 2000 ). Interpersonal barriers also exist, including a lack of trust between EHS staff and parents, family stress, teachers’ job stress and dissatisfaction, and parent-teacher differences in caregiving beliefs (Hooper et al, 2022 ). For center-based EHS programs to impact caregiving across home and school contexts, it is necessary to develop coordinated programming that addresses these barriers.…”
Section: The Need For Coordinated Programmingmentioning
confidence: 99%
“…Structural barriers impact family involvement in programming, including a lack of flexibility in parents’ work schedules and difficulty arranging family involvement activities outside of program hours (Golas et al, 2006 ; Spoth & Redmond, 2000 ). Interpersonal barriers also exist, including a lack of trust between EHS staff and parents, family stress, teachers’ job stress and dissatisfaction, and parent-teacher differences in caregiving beliefs (Hooper et al, 2022 ). For center-based EHS programs to impact caregiving across home and school contexts, it is necessary to develop coordinated programming that addresses these barriers.…”
Section: The Need For Coordinated Programmingmentioning
confidence: 99%
“…The home learning environment, as an effective combination of activities and resources at home, is a major factor in the development of children’s social–emotional competence ( Domitrovich et al, 2017 ; Lehrl et al, 2020 ). Previous studies have shown that factors such as socioeconomic status, family functions, family activities, and parenting styles influence the development of young children’s social–emotional competence ( Liu J. et al, 2020 ; Schapira and Aram, 2020 ; Hooper et al, 2022 ). However, the home learning environment is greater than just the sum of its component environmental elements.…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, en un estudio en el que se analizó los perfiles de estrés, apoyo social, bienestar psicológico y funcionamiento familiar se encontró que los niños con un perfil de alto funcionamiento familiar y bajo estrés tenían destrezas socioemocionales más adecuadas (Hooper et al, 2022). Además, en una revisión bibliográfica acerca de adolescentes transgéneros, se llegó a la conclusión que el factor protector esencial del bienestar psicológico es el apoyo percibido, en especial el familiar; no obstante, cuando este se percibe como rechazo se torna en factor de riesgo para esta población (Cárdenas et al, 2021).…”
Section: Introductionunclassified